2017
DOI: 10.1007/s00192-017-3488-z
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence in female outpatients in Singapore

Abstract: Despite the high prevalence of UI, only about 41% of UI sufferers had sought medical attention before. Common barriers included embarrassment, fear of surgery and misconceptions. This study emphasizes the need for policy development for UI prevention and management in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
6
0
4
Order By: Relevance
“…In addition, the present study found that scores on the IIQ‐7 and for the physical activity, traveling, social relations and mental health domains were lower for individuals who did not see a doctor because they thought that urinary leakage was normal. In other studies, individuals with higher scores on life quality scales that indicate their life is negatively affected by UI more often see a doctor . Thus, in the present study, although individuals whose QoL was negatively affected by UI visited a doctor, those who were less affected believed that UI is a natural result of aging.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In addition, the present study found that scores on the IIQ‐7 and for the physical activity, traveling, social relations and mental health domains were lower for individuals who did not see a doctor because they thought that urinary leakage was normal. In other studies, individuals with higher scores on life quality scales that indicate their life is negatively affected by UI more often see a doctor . Thus, in the present study, although individuals whose QoL was negatively affected by UI visited a doctor, those who were less affected believed that UI is a natural result of aging.…”
Section: Discussionsupporting
confidence: 44%
“…In other studies, individuals with higher scores on life quality scales that indicate their life is negatively affected by UI more often see a doctor. 10,25,[30][31][32][33][34] Thus, in the present study, although individuals whose QoL was negatively affected by UI visited a doctor, those who were less affected believed that UI is a natural result of aging.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Segundo Talasz et al (2008) A prevalência de IU pode variar entre 24 e 41% em mulheres de 65 anos (BRESEE et al, 2014;GOODE et al, 2008), já em um estudo nacional, foi verificado uma prevalência de 27% em mulheres com idade média de 51 anos (AMARO et al,2009). Em um segundo estudo nacional conduzido por Silva e Lopes (2009) CAAGBAY et al, 2017, JACKSON et al, 2017NEELS et al, 2016aNEELS et al, , 2016b BROWN et al, 1996;LASSERRE et al, 2009;LUO et al, 2017;NYGAARD;BARBER, 2008;ROGERS, 2008).…”
Section: Conhecimento Sobre Os Músculos Do Assoalho Pélvicounclassified
“…Em estudo realizado porDelancey et al (2008) foi constatado que a pressão de fechamento uretral foi o parâmetro com maior associação a causa da IUE. IU afeta negativamente a qualidade de vida devido a sentimentos de constrangimento, vergonha, medo do odor proveniente da perda urinária levando ao isolamento de atividades sociais e recreativas, tais fatos fazem com que esta mulheres criem uma barreira para buscar cuidados de saúde(LUO et al, 2017;SINCLAIR;RAMSAY, 2011;TEUNISSEN et al, 2006).Estudos realizados em diversos países, como França, Índia, Taiwan, Singapura, Emirados Árabes Unidos e Sri Lanka também verificam que o constrangimento, a vergonha ou timidez são barreiras para que as mulheres que sofrem com a IU não procurem por cuidados de saúde(ELBISS;OSMAN;HAMMAD, 2013;HSIEH et al, 2008;LASSERRE et al, 2009;LUO et al, 2017;PRABHU;SHANBHAG, 2013;PERERA et al, 2014).O conhecimento das mulheres sobre a IU parece ser escasso(LIAPIS et al, 2010; MANDOMBWE et al, 2010). Em uma pesquisa realizada na Grécia porLiapis et al (2010) incluindo 2000 mulheres com idade entre 20 e 80 anos, 27% delas apresentaram relatos de IU e a maior prevalência ocorreu entre 60 a 80 anos.…”
unclassified